Arterial and Venous Thrombosis Complicated in COVID-19: A Retrospective Single Center Analysis in Japan - Oba, Seiya; Hosoya, Tadashi; Amamiya, Miki; Mitsumura, Takahiro; Kawata, Daisuke; Sasaki, Hirokazu; Kamiya, Mari; Yamamoto, Akio; Ando, Takahiro; Shimada, Sho; Shirai, Tsuyoshi; Okamoto, Tsukasa; et al. (Frontiers in Cardiovascular Medicine, 2021)
[Background] Thrombosis is a characteristic complication in Coronavirus disease 2019 (COVID-19). Since coagulopathy has been observed over the entire clinical course, thrombosis might be a clue to understanding the specific pathology in COVID-19. Currently, there is limited epidemiological data of COVID-19-associated thrombosis in the Japanese population and none regarding variant strains of SARS-CoV-2. Here, we elucidate the risk factors and the pattern of thrombosis in COVID-19 patients. [Methods] The patients consecutively admitted to Tokyo Medical and Dental University Hospital with COVID-19 were retrospectively analyzed. SARS-CoV-2 variants of concern/interest (VOC/VOI) carrying the spike protein mutants E484K, N501Y or L452R, were identified by polymerase chain reaction-based analysis. All thrombotic events were diagnosed by clinical symptoms, ultrasonography, and/or radiological tests. [Results] Among the 516 patients, 32 patients experienced 42 thromboembolic events. Advanced age, severe respiratory conditions, and the several abnormal laboratory markers, were associated with the development of thrombosis. While thrombotic events occurred in 13% of the patients with severe respiratory condition, those events still occurred in 2.5% of the patients who did not require oxygen therapy. Elevated D-dimer and ferritin levels on admission were independent risk factors of thrombosis (Adjusted odds ratio 9.39 and 3.11, 95% confidence interval 2.08-42.3, and 1.06-9.17, respectively). Of the thrombotic events, 22 were venous, whereas 20 were arterial. While patients with thrombosis received anticoagulation and anti-inflammatory therapies with higher proportion, the mortality rate, organ dysfunctions, and bleeding complications in these patients were higher than those without thrombosis. The incidence of thrombosis in COVID-19 became less frequent over time, during replacement of the earlier strains of SARS-CoV-2 by VOC/VOI and during increased use of anticoagulatory therapeutics. [Conclusion] This study elucidated that elevated D-dimer and ferritin levels are useful biomarkers of thrombosis in COVID-19 patients. The comparable incidence of arterial thrombosis with venous thrombosis and the development of thrombosis in less severe patients required further considerations to the management of Japanese COVID-19 patients. Further studies would be required to identify high-risk populations and establish appropriate interventions for thrombotic complication in COVID-19.